The Effect of Digital Marketing and Influencers on Purchasing Decisions for SMEs Culinary Products Spaghetti Tulang Lampung - Rizky, Alivia; Asnusa, Soraya (Prosiding International conference on Information Technology and Business (ICITB), 2023)
Technological advancements and the development of social media have changed the marketing landscape, especially for Micro, Small and Medium Enterprises (SMEs). The purpose of this study is to explore the effect of digital marketing and the role of influencers in influencing purchasing decisions for SMEs products "Spaghetti Tulang Lampung" This regional culinary product has become one of the culinary icons in the Lampung area, and SMEs that produce Spaghetti Tulang Lampung are trying to utilize digital platforms to increase sales and increase their brand awareness. This research uses a quantitative approach with a causality approach method or causal relationship, The research sample consists of consumers who have purchased Spaghetti Tulang Lampung products and have been exposed to digital marketing and influencer content. Data was collected through questionnaires distributed online to respondents and the analysis tool in this study uses SPSS to prove the relationship between digital marketing and the role of influencers in influencing purchasing decisions for SMEs products "Spaghetti Tulang Lampung". The findings will provide valuable insights for Lampung Spaghetti Tulang SMEs and similar SMEs looking to utilize digital marketing and influencers in their marketing strategies. An effective digital marketing strategy and good collaboration with influencers can help boost sales and increase brand visibility in an increasingly competitive market.Â Keywords-Digital Marketing, Influencer, Purchase Decision